2018
DOI: 10.1007/s00592-017-1091-x
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies against zinc transporter 8 are related to age and metabolic state in patients with newly diagnosed autoimmune diabetes

Abstract: AimsTo assess the prevalence of ZnT8-ab and its correlation to other autoimmune markers and diabetic ketoacidosis occurrence in children and adults with T1DM onset. MethodsThe study included 367 patients (218 children; 149 adults) at the T1DM onset. Selected diabetes-related autoantibodies such as GAD-ab, IA2-ab, ZnT8-ab were tested before the initiation of insulin therapy. Diabetic ketoacidosis was defined as glucose concentration > 13.9 mmol/l, pH < 7.30, concentration of HCO3 < 15 mmol/l, presence of ketone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 45 publications
(43 reference statements)
4
20
1
1
Order By: Relevance
“…The mean age at the onset of diabetes was similar to an Indian population, and the distribution of gender was also similar [8]. There was a higher frequency of ZnT8A in males in the current study, which contrasts with a number of studies that reported a higher frequency in women or even documented no difference between genders with T1DM that was noticed by Eisenbarth et al probably because of difference in gender distribution in these studies [15,[19][20][21].…”
Section: Discussionsupporting
confidence: 53%
“…The mean age at the onset of diabetes was similar to an Indian population, and the distribution of gender was also similar [8]. There was a higher frequency of ZnT8A in males in the current study, which contrasts with a number of studies that reported a higher frequency in women or even documented no difference between genders with T1DM that was noticed by Eisenbarth et al probably because of difference in gender distribution in these studies [15,[19][20][21].…”
Section: Discussionsupporting
confidence: 53%
“…In addition, the prevalence of islet autoantibody positivity in T1DM appeared to be correlated with age and clinical presentation. In a recent study in Caucasian subjects, ZnT8A and IA2A were commonly detected in children with T1DM, whereas adults had a significantly frequently higher GADA titer . Furthermore, ZnT8A are associated with more acute diabetes onset and DKA .…”
Section: Discussionmentioning
confidence: 91%
“…In a recent study in Caucasian subjects, ZnT8A and IA2A were commonly detected in children with T1DM, whereas adults had a significantly frequently higher GADA titer. 18 Furthermore, ZnT8A are associated with more acute diabetes onset and DKA. 18 Similarly, ZnT8A are more prevalent in younger (≤20 years) new-onset Japanese patients, compared with patients with age at onset >20 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the majority of those with T1DM have positive antibodies at presentation, some do not and presumably develop them later. 22,29 Thus, obese individuals with negative autoantibodies may be mistaken for having T2DM but may in fact have T1DM. In patients with negative antibodies at presentation but a clinical course suggestive of T1DM, the authors recommend rechecking antibodies to help determine the actual diagnosis.…”
Section: Etiology and Diagnosis Of Diabetesmentioning
confidence: 99%